Revealing the role of excited state nuclear coherence in the photoisomerisation of bacteriorhodopsin by population assisted impulsive Raman - Liebel, M; Kukura, P (IEEE, 2013)
The 13-cis to all-trans photoisomerisation of the retinal chromophore in bacteriorhodopsin (bR) is a prototypical ultrafast isomerisation process[1]. Within the protein, the reaction is faster, more efficient and more specific than in solution. This variation of chemical reactivity and specificity has spurned decades of spectroscopic investigations to unravel the origin of retinal reactivity in bR. The key remains the reactive entity in the process: the potential energy surface of the reactive excited electronic state that is populated upon absorption of a visible photon. Despite application of numerous ultrafast electronic and vibrational techniques,[2-4] the ultrafast structural evolution of the chromophore after excitation remains effectively unknown. Similarly, the relaxed vibrational structure of the excited state is yet to be determined. © 2013 IEEE.